REORIENTASI PEMBELAJARAN AGAMA: STRATEGI SISTEMATIK MENUJU INTERNALISASI NILAI-NILAI ISLAM RAHMATAN LIL 'ALAMIN - FATMA AMALIA RAHMA (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Contemporary Islamic Religious Education (IRE) instruction still tends to focus on cognitive and formalistic approaches that prioritize the transfer of knowledge, thereby failing to fully address the challenges of extremism and social polarization emerging in society. This article aims to formulate a systematic strategy to reorient religious instruction toward internalizing the values ​​of Islam as Rahmatan lil 'Alamin Islam that brings mercy to all creation. Employing a descriptive qualitative method based on library research, the study identifies three key areas for reorientation: reconstructing the curriculum based on values ​​of inclusivity and multiculturalism; transforming teaching methods to be dialogic and reflective; and restructuring the learning environment by strengthening school culture. The findings indicate that instilling values ​​of peace, tolerance, and humanity can be effectively achieved through internalization strategies that integrate the cognitive, affective, and psychomotor domains. Consequently, reorienting IRE instruction requires teachers to act not merely as conveyors of material but as facilitators who foster the realization of religious moderation.